Praktik Sosial BSI Dalam Program Pengembangan UMKM di Kota Banda Aceh (Studi Kasus UMKM Capli Sambal Ijo Aceh) - Malika, Della; Bukhari; Nusuary, Firdaus Mirza; Barakah, Fadlan (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2023)
This study examines the social practices in the Micro, Small, and Medium Enterprises (MSME) development program conducted by Bank Syariah Indonesia (BSI), exploring the relationship between agents and the structures within it. The objective of this research is to analyze the forms of social practices occurring in the MSME development program provided by BSI to MSMEs in the city of Banda Aceh, specifically focusing on the MSME known as Capli Sambal Cabe Ijo. Within this research, social practices tend to be dominated by the role of agents controlling the S-D-L structure, with agent motivation reflected in discursive awareness. The theoretical foundation for this study is Anthony Giddens' structuration theory, which identifies agents with various forms of awareness, including unconscious motives, discursive awareness, and practical awareness. Giddens also delineates the definition of structure into three propositions: Significance, Domination, and Legitimacy. The relationship between agents and structure forms a recurrence across space and time as a social practice. The research methodology employed is qualitative, utilizing a case study approach. The findings indicate that significance without the support of domination and legitimacy can lead to emptiness or the ineffectiveness of that significance. In the context of BSI UMKM Center as the Expert Agent and UMKM as the Lay Agent, three S-D-L propositions automatically shape social practices. Discursive awareness from each agent continually occurs across space and time, ensuring the sustainability of recurrent social practices. To address the issues raised in this research, both UMKM and BSI are expected to maintain the recurrence of social practices to ensure the ongoing success of the program and the preservation of the structure. This is necessary for the continuous perpetuation of social practices. Keywords: Social Practices, MSMEs, BSI, Agents and Structures